1986
DOI: 10.1038/sc.1986.17
|View full text |Cite
|
Sign up to set email alerts
|

The neurovisceral and electrodiagnostic evaluation of patients with thoracic spinal cord injury

Abstract: SutntnaryWe studied nine patients with complete thoracic spinal cord injury in order to investigate distal electrophysiologic and end organ function. Studies included motor and sensory nerve conduction velocities, spinal and cortical somatosensory evoked responses, bulbocavernosus reflex responses, cystometry and colonic compliance, motor and myoelectrical activity. These studies confirmed an intact peripheral nervous system, as well as normal nerve root, cauda equina, conus medullaris and distal spinal cord f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…[9][10][11][12][13] SCI patients lose a variable proportion of their extrinsic autonomic innervation to their gut, depending on the level of injury, whereas the intrinsic enteric nervous system remains intact. 3 The gut intrinsic nervous system may lose integrity with time because of the loss of extrinsic supply.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] SCI patients lose a variable proportion of their extrinsic autonomic innervation to their gut, depending on the level of injury, whereas the intrinsic enteric nervous system remains intact. 3 The gut intrinsic nervous system may lose integrity with time because of the loss of extrinsic supply.…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepines have not previously been shown to increase the risk of constipation in non-injured subjects 33,37 and this study ®nding may be confounded by increased administration to individuals who are Frankel grade A or B. The ®nding that individuals with history of previous urinary outlet surgery had a greater risk of reporting di culty with evacuation may re¯ect the shared innervation between bladder and lower gut; hyperre¯exic volume-pressure abnormalities have been documented in both the colon and bladder in individuals with cervicothoracic lesions, 8,9,23 and persons with anorectal dyssynergia also tend to have concomitant bladder detrusorsphincter dyssynergia. 3 Stone et al found that 72% of individuals with di culty with evacuation had had transurethral sphincterotomy.…”
Section: Discussionmentioning
confidence: 74%
“…Physiological studies have generally shown that the postprandial increase in colonic spike potentials corresponding to the gastrocolic re¯ex, is absent in individuals with cervicothoracic lesions. 8,9,47 However, these clinical ®ndings would suggest that patients should nevertheless be encouraged to administer their bowel program within 45 min of ingesting a meal, or hot or carbonated¯uids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations